2021
DOI: 10.2478/fhort-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen, phosphorus and potassium deficiencies on some morphological and physiological properties and nutrient uptake by two almond rootstocks

Abstract: A soilless culture and completely randomised two-factorial experiment was carried out to investigate the effect of nitrogen (N), phosphorus (P) and potassium (K) deficiencies on macronutrient uptake and to determine some characteristics of Prunus dulcis L. (bitter almond: BA) and Prunus scoparia L. (Alook: AL) seedlings. Seedlings in pots containing perlite were irrigated with half-strength, N-, P- and K-free Hoagland solutions for 12 wk. Results showed that N deficiency decreased the N and Ca levels and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In turn, there may be an opposite relationship with the NO 3 − ion because potassium is also an antagonist in relation to magnesium, which is also not indifferent to growth, development, and, as a consequence, crop yield [54]. However, too low of potassium fertilisation can also limit the uptake of many macro-and microelements by plants because the right ratio between potassium, calcium, magnesium, and sodium determines the correct water management of plants [55]. Correct ratios between fertiliser components (balancing their negative interactions) are therefore essential for high crop yields.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, there may be an opposite relationship with the NO 3 − ion because potassium is also an antagonist in relation to magnesium, which is also not indifferent to growth, development, and, as a consequence, crop yield [54]. However, too low of potassium fertilisation can also limit the uptake of many macro-and microelements by plants because the right ratio between potassium, calcium, magnesium, and sodium determines the correct water management of plants [55]. Correct ratios between fertiliser components (balancing their negative interactions) are therefore essential for high crop yields.…”
Section: Discussionmentioning
confidence: 99%
“…Coskun et al [64] showed the antagonistic effect of potassium on nitrogen nutrition in the form of NH 4 + , and the synergistic effect between K + and NO 3 − ions. A deficiency of potassium or other nutrients in the soil can limit the content of potassium and other elements in plants, such as nitrogen, calcium and sometimes phosphorus [65]. Therefore, when N fertilization is limited, the potassium content in plants increases and the calcium content decreases.…”
Section: Discussionmentioning
confidence: 99%